Guwosari Village Community Empowerment in Overcoming Stunting Post Covid-19 Pandemic - Anafrin Yugistyowati; Yulinda Kurniasari; Resti Kurnia Triastanti; Atika Hadiningrum Nasution; Naufal Adam; Ardha Syafaiyadi (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Stunting children are faced with various health problems and child development. Mothers as primary caregivers are expected to have a good awareness and understanding of the care of their children. The current condition with the COVID-19 outbreak will also directly impact the health quality of stunting children. The problem of stunting children requires integrated education efforts with multi-sectoral involvement and family participation. This PKM activity was carried out through several stages of preparation, training and evaluation of activities for 165 health cadres and 105 families with stunting children in Guwosari village, Pajangan, Bantul. PKM activities in the form of training on the manufacture of PMT for toddlers made from local food; Stimulation, Detection, and Early Intervention (SDIDTK) training for children; and health promotion training. The results of PKM activities have a social impact on increasing the knowledge and skills of health cadres and families; In addition, indirectly that the quality of health and growth and development of stunting children is maintained, then community activities in this case families with stunting children in the utilization of health services because of illness problems in children can be minimized, so that the family economy will be maintained for the use of other needs. Sustainability of this PKM program, that the role of health cadres in handling stunting requires ongoing assistance and evaluation from the Guwosari Village Head, the Health Office and the local Community Health Center.